1987
DOI: 10.1177/030089168707300503
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thymidine Kinase and Beta-2 Microglobulin in Monoclonal Gammopathies

Abstract: We evaluated the serum thymidine kinase (TK) and beta-2 microglobulin (beta-2) levels of 22 patients with monoclonal gammopathy of undetermined significance (MGUS) and of 29 patients with multiple myeloma (MM). Both parameters were significantly lower in MGUS than in MM patients and in early (stage I + II) than in advanced (stage III) MM. TK was also lower in MGUS than in stage I MM (p less than 0.025). A seven-fold increase of TK level was documented in one patient who developed a full blown picture of MM 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The need to reconsider routinely used staging systems so as to account for the most recent prognostic factors is widely recognized (15, 16). Several new parameters have recently emerged as possible prognostic factors: plasma cell morphology (17), plasma cell labeling index (5,18,19,20), DNA hypodiploidy (21), RNA index (21), plasma cell antigens (22,23,24), oncogene expression (25), light chain isotype suppression (26), S-LDH (15, 27) S-thymidine kinase (28,29) and S-B-2M (30). With few exceptions (31) most reports have shown that S-P-2M was the most powerful independent prognostic factor (32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The need to reconsider routinely used staging systems so as to account for the most recent prognostic factors is widely recognized (15, 16). Several new parameters have recently emerged as possible prognostic factors: plasma cell morphology (17), plasma cell labeling index (5,18,19,20), DNA hypodiploidy (21), RNA index (21), plasma cell antigens (22,23,24), oncogene expression (25), light chain isotype suppression (26), S-LDH (15, 27) S-thymidine kinase (28,29) and S-B-2M (30). With few exceptions (31) most reports have shown that S-P-2M was the most powerful independent prognostic factor (32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The complete clinical, radiological and laboratory evaluation of patients with plasma cell dyscrasias was carried out according to a protocol that also require special examinations, such as P2-microglobulin and thymidine kinase level determination (Ucci et al, 1987) and BMPC proliferative activity evaluation (as the percentage labelled with in vitro BUDR and with the monoclonal antibody Ki-67). In all patients, BMPC% was counted on imprints of BM sample aspirated for FCM and p21 evaluation.…”
Section: Materals and Methodsmentioning
confidence: 99%